Neurogenin2‐d4Venus and Gadd45g‐d4Venus transgenic mice: Visualizing mitotic and migratory behaviors of cells committed to the neuronal lineage in the developing mammalian brain. (9th April 2014) - Kawaue, Takumi; Sagou, Ken; Kiyonari, Hiroshi; Ota, Kumiko; Okamoto, Mayumi; Shinoda, Tomoyasu; Kawaguchi, Ayano; Miyata, Takaki
<x xml:space="preserve">Abstract</x> To achieve highly sensitive and comprehensive assessment of the morphology and dynamics of cells committed to the neuronal lineage in mammalian brain primordia, we generated two transgenic mouse lines expressing a destabilized (d4) Venus controlled by regulatory elements of the Neurogenin2 (Neurog2) or Gadd45g gene. In mid‐embryonic neocortical walls, expression of Neurog2‐d4Venus mostly overlapped with that of Neurog2 protein, with a slightly (1 h) delayed onset. Although Neurog2‐d4Venus and Gadd45g‐d4Venus mice exhibited very similar labeling patterns in the ventricular zone (VZ), in Gadd45g‐d4Venus mice cells could be visualized in more basal areas containing fully differentiated neurons, where Neurog2‐d4Venus fluorescence was absent. Time‐lapse monitoring revealed that most d4Venus+ cells in the VZ had processes extending to the apical surface; many of these cells eventually retracted their apical process and migrated basally to the subventricular zone, where neurons, as well as the intermediate neurogenic progenitors that undergo terminal neuron‐producing division, could be live‐monitored by d4Venus fluorescence. Some d4Venus+ VZ cells instead underwent nuclear migration to the apical surface, where they divided to generate two d4Venus+ daughter cells, suggesting that the symmetric terminal division that gives rise to neuron pairs at the apical surface can be reliably live‐monitored. Similar lineage‐committed cells were observed in other developing neural regions including retina, spinal cord, and cerebellum, as well as in regions of the peripheral nervous system such as dorsal root ganglia. These mouse lines will be useful for elucidating the cellular and molecular mechanisms underlying development of the mammalian nervous system.